Pneumothorax following rupture of lung cavity due to aspergillosis in a critically ill patient (Bangladesh Critical Care Journal, 2020)
The incidence of fungal infection in intensive care units have been increasing over the years and Aspergillosis is one of the common fungal infections in the ICUs. It is a challenge for critical care experts to diagnose fungal infections on time and initiate appropriate management strategy to prevent adverse outcomes. Fungal infections may be notorious in not being diagnosed with a chest X ray alone as fungal infections related cavitary lesions may not always be seen in a chest X ray, necessitating the need of a CT Scan early on in the course of the illness. A chest CT scan may further be justified if the patient is not responding to a protracted course of higher antibiotics. Any delay in diagnosis may lead to poor outcome. Here we present a case who underwent subtotal gastrectomy for adenocarcinoma of stomach and presented one month later with fever, cough and shortness of breath. The patient was subsequently managed in the ICU but later expired following pneumothorax due to rupture of lung cavity associated with aspergillosis.Bangladesh Crit Care J September 2020; 8(2): 131-133